2022
DOI: 10.1007/s11739-022-02993-z
|View full text |Cite
|
Sign up to set email alerts
|

Mortality prediction using a modified R2CHA2DS2-VASc score among hospitalized COVID-19 patients

Abstract: The CHA 2 DS 2 -VASc score incorporates several comorbidities which have prognostic implications in COVID-19. We assessed whether a modified score (M-R 2 CHA 2 DS 2 -VASc), which includes pre-admission kidney function and male sex, could be used to classify mortality risk among people hospitalized with COVID-19. This retrospective study included adults admitted for COVID-19 between March and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Indeed, in our population, each decrease in 10 kg/ Kg 2/3 upper arm muscle strength was associated to a nearly twofold risk of endotracheal intubation. We also found, in line with previous reports [19], that a positive history of CV diseases and reduced eGFR also independently predicted adverse clinical outcomes in COVID-19-related pneumonia.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, in our population, each decrease in 10 kg/ Kg 2/3 upper arm muscle strength was associated to a nearly twofold risk of endotracheal intubation. We also found, in line with previous reports [19], that a positive history of CV diseases and reduced eGFR also independently predicted adverse clinical outcomes in COVID-19-related pneumonia.…”
Section: Discussionsupporting
confidence: 93%
“…Recent findings showed that the CHA 2 DS 2 -VASc score and its modified forms can differentiate patients at higher risk of worse outcome in course of SARS-CoV-2 infection [16][17][18]. Our comment concerns the article by Levy et al in the current issue of Internal and Emergency Medicine that evaluated the role of the modified R 2 CHA 2 DS 2 -VASc (M-R 2 CHA 2 DS 2 -VASc) score on the prediction of mortality in hospitalized patients with SARS-CoV-2 infection [19].…”
mentioning
confidence: 93%
“…MHD patients are immunocompromised and may have other risk-factors associated with their primary renal disease, such as older age, diabetes, hypertension, etc. As such, they were found to be at increased risk for severe disease and mortality [ 16 , 17 , 18 , 19 ]. Therefore, with the release of the SARS-CoV-2 mRNA vaccine, MHD patients were prioritized for vaccination.…”
Section: Introductionmentioning
confidence: 99%